KOMITMEN KERJA DALAM MEDIASI ETOS KERJA TERHADAP KINERJA PEGAWAI DINAS PERDAGANGAN PERINDUSTRIAN DAN KETENAGAKERJAAN KABUPATEN SERAM BAGIAN BARAT - Alfred Arysta Kamelane; Elake Nataniel; Mike J. Rolobessy (Social and Political Sciences Faculty, Widya Gama Mahakam Samarinda University, 2025)
This study aims to analyze the role of work commitment in mediating work ethic on employee performance at the Trade, Industry and Manpower Office of West Seram Regency. This study uses a descriptive-quantitative approach with a causal correlation type, meaning that the relationship between the independent variable and the dependent variable is a causal relationship. The population used in this study were all employees at the Maluku Province BKD, totaling 144 people. The sampling method uses the Issac and Michael sample table, where if the population is 144 people, then at a 95% confidence level, the sample size is 100 people determined by simple random sampling using a lottery technique. Data were analyzed using path analysis. SThe results of the study concluded that (1) Work ethic has a positive and significant effect on the work commitment of employees of the Industry, Trade and Manpower Service of West Seram Regency, (2) Work ethic has a positive and significant effect on the performance of employees of the Industry, Trade and Manpower Service of West Seram Regency, (3) Work commitment has a positive and significant effect on the performance of employees of the Industry, Trade and Manpower Service of West Seram Regency and (4) Work ethic has a positive and significant effect on performance through the work commitment of employees of the Industry, Trade and Manpower Service of West Seram Regency.